The optimal true ileal digestible lysine and threonine requirement for nursery pigs between 25 and 55 lb - N A Lenehan; J L Usry; C W Hastad; M R Barker; N Z Frantz; C N Groesbeck; B W James; T P Keegan; K R Lawrence; M G Young; Michael D Tokach; Robert D Goodband; et al. (Kansas Agricultural Experiment Station Research Reports, 2003)
A total of 360 pigs (initially 22.2 lb and 31 d of age) was used in a 21-d growth assay. This trial was conducted as a combination of two separate trials in order to simultaneously examine both the true ileal digestible lysine and true ileal digestible threonine requirement and determine the appropriate threonine:lysine ratio. The first part of the trial consisted of five treatments with increasing dietary lysine (1.0. 1.1, 1.2, 1.3 and 1.4% true digestible lysine). The second part consisted of five treatments with increasing dietary threonine (0.66, 0.72, 0.78, 0.84 and 0.91% true ileal digestible threonine). The highest level of both lysine and threonine (1.4% and 0.91% respectively) served as a positive control, and this diet was combined as one treatment to give a total of nine treatments. Average daily gain increased to 1.3% true ileal digestible lysine, and then plateaued, while ADG increased to 0.78% true ileal digestible threonine, suggesting a threonine:lysine ratio of 60% for ADG. Increasing dietary lysine improved F/G linearly through 1.4% true ileal digestible lysine, while F/G improved up to a level of 0.84% true ileal digestible threonine. Using a level of 1.4% true ileal digestible lysine, a threonine:lysine ratio of approximately 60% is implicated for F/G. Amino acid and plasma urea N values were measured on d 10 of the trial. Plasma lysine concentrations were maintained steadily as the true ileal digestible lysine level increased, with a slight increase in plasma lysine concentration observed as the true ileal digestible lysine level increased from 1.3% to 1.4%. A linear increase (P<.0001) in plasma threonine concentration was observed as true ileal digestible threonine increased from 0.66% to 0.91%. Plasma urea N decreased linearly (P<0.0003) with increasing true ileal digestible lysine. As true ileal digestible threonine increased, there was no difference seen in plasma urea N concentration. Following analysis of the data, a true ileal digestible threonine to lysine ratio of 60% is suggested. A second study is in progress where the higher true digestible lysine level of 1.5% is used to verify trial results.; Swine Day, 2003, Kansas State University, Manhattan, KS, 2003
Keywords: Swine day; 2003; Kansas Agricultural Experiment Station contribution; no. 04-120-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 920; Threonine; Lysine; Nursery pigs; Swine